Magnetic Bead Capture Eliminates PCR Inhibitors in Samples Collected from the Airborne Environment, Permitting Detection of Pneumocystis carinii DNA - Maher, Nancy (American Society for Microbiology, 2001)
PCR detection methods are useful in studies of organisms not amenable to culture. Inhibitors in environmental samples can interfere with such assays. We describe a magnetic bead DNA capture protocol that removes inhibitors from outdoor air samples, maintaining the sensitivity of a 16S Pneumocystis carinii mitochondrial rRNA gene-based PCR.